Indumentária como expressão da identidade gay: a pluralidade das masculinidades na praça roosevelt - Bernardo, Yuri Demartini (2025)
This dissertation investigates clothing as an expression of gay identities in Praça Roosevelt, São Paulo, an urban space where dressing is configured as a social, cultural and identity practice. The research, of ethnographic inspiration and supported by references from urban anthropology and audiovisual, analyzes how clothing styles, accessories and aesthetic performances of patrons reflect personal and collective experiences of the LGBTQIAPN+ community. The results show that clothing goes beyond the aesthetic dimension, registering the body socially, mediating relations of sociability, establishing symbolic borders and constituting identity narratives. The empirical analysis was organized in five axes: clothing as a cultural language; body styles and the body dressed as an identity support; handbags and shoes as markers of consumption, status and lifestyle; the that both reiterate and tension hegemonic standards; and the articulation between identity and consumption, understood as cultural, political and performative practice. In dialogue with authors such as Roland Barthes, Pierre Bourdieu, Judith Butler, Stuart Hall, Leandro Colling and Mike Featherstone, the dissertation demonstrates that fashion and clothing are not restricted to questions of taste or market. In the case of gay men, they constitute a language of resistance, a space for experimentation and an instrument of negotiation with social norms, producing belonging, projecting singularities and enhancing the expression of diversity.